The Relationship Between Residential Quality of Life and Socioeconomic Status in England. (January 2014) - Campanera, Josep M.; Nobajas, Alexandre; Higgins, Paul
This article explores the quintessential "person–environment" relationship that forms the core of the subdiscipline of social geography within the context of a national accountability shift from state to society in England. Two Audit Commission datasets are mined to establish homogeneous clusters of residential socioeconomic status and quality of life status before being cross-tabulated to detect genuine issues that affect each characteristic locality. In three of the four cross-tabulations, significant differences on economic well-being, life-long learning, and health distinguish correspondences, whereas in the other, less tangible, case, such factors as the use of cultural facilities, community cohesion, and people's access to work seem to matter. The implications for research, policy, and practice are duly considered.